Преобразование дробей .

Домножение на -1 .








1.    \(\dfrac{a-1}{1-a} \)


  

\( -1 \)

\( \dfrac{a-1}{1-a}=\dfrac{(-1)\cdot(a-1)}{(-1)\cdot(1-a)}=\dfrac{-a+1}{(-1)\cdot(1-a)}=\dfrac{1-a}{(-1)\cdot(1-a)}=\dfrac{1}{(-1)}=-1 \)


ПОЗЖЕ



2.   \(\dfrac{a-b}{b-a} \)


  

\( -1 \)

\(\dfrac{a-b}{b-a}=\dfrac{(-1)\cdot(a-b)}{(-1)\cdot(b-a)}=\dfrac{-a+b}{(-1)\cdot(b-a)}=\dfrac{b-a}{(-1)\cdot(b-a)}=\dfrac{1}{(-1)}=-1 \)


ПОЗЖЕ



3.   \(\dfrac{5a-b}{b-5a} \)


  

\( -1 \)

\(\dfrac{5a-b}{b-5a}=\dfrac{(-1)\cdot(5a-b)}{(-1)\cdot(b-5a)}=\dfrac{-5a+b}{(-1)\cdot(b-5a)}=\dfrac{b-5a}{(-1)\cdot(b-5a)}=\dfrac{1}{(-1)}=-1 \)


ПОЗЖЕ




4.    \( \dfrac{m-n}{mn}\cdot \dfrac{2mn}{mn-m^2}\)


  

\( - \dfrac{2}{m} \)

\( \dfrac{m-n}{mn}\cdot \dfrac{2mn}{mn-m^2}= \dfrac{m-n}{1}\cdot \dfrac{2}{m(n-m)}= \dfrac{n-m}{-1}\cdot \dfrac{2}{m(n-m)}=\)

\( = \dfrac{1}{-1}\cdot \dfrac{2}{m} =- \dfrac{2}{m} \)


ПОЗЖЕ




5.    \( \dfrac{a+b+c+d}{x-a} + \dfrac{d+a+b+c}{a-x} \)


  

\( 0 \)

\( \dfrac{a+b+c+d}{x-a} + \dfrac{d+a+b+c}{a-x} = \dfrac{a+b+c+d}{x-a} - \dfrac{d+a+b+c}{x-a}= \)

\(= \dfrac{a+b+c+d-d-a-b-c}{x-a} =\dfrac{0}{x-a}=0 \)



ПОЗЖЕ